Phlegra Simon, 1876, Phintella Strand 1906 and Yamangalea Maddison, 2009 (Arachnida: Araneae: Salticidae)— new species and new generic records for Australia - Żabka, Marek (Zootaxa, 2012)
Phlegra Simon, Phintella Strand and Yamangalea Maddison are newly recorded from Australia, each genus beingrepresented here by one new species: Phlegra proszynskii, Phintella monteithi and Yamangalea lubinae. The diagnoses and descriptions are provided and remarks on distribution are given.